Remineralization Potential of Grape Seed Extract on Artificial Enamel Caries Lesions - Ozden, Serif Alpcan; Oz, Esra (Journal of Dentistry Indonesia, 2024)
Objective: This study aimed at a comparative analysis of the remineralization potential of grape seed extract (GSE) alone, together with casein phosphopeptide-amorphous calcium phosphate (CPP-ACP) and/or acidulated phosphate fluoride (APF). Methods: The samples were randomly divided into seven groups according to the treatment used: 25% GSE, 1.23% APF (Gelato APF gel), and CPP-ACP (GC Tooth Mousse). The samples in group 7 received no treatment as a control group. All specimens were subjected to pH cycling for two weeks. Surface microhardness analyses were performed at baseline, after demineralization and remineralization. Data were analyzed using one-way analysis of variance (ANOVA), Post Hoc Bonferroni, and Repeated measures of ANOVA tests (0.05). Results: There was a statistically significant difference between the mean microhardness values of the groups after remineralization (p < 0.05). The difference was between groups 2 and 7. According to the surface microhardness values measured at baseline, after demineralization, and after remineralization within groups 3, 5, and 6, the difference was due to all measurement times. The mean microhardness values were highest at baseline and the lowest after demineralization. Conclusion: This study concluded that grape seed extract with other agents can increase the remineralization efficiency, however, it is essential to support the results with in vivo studies.